Preventing Foodborne Illness: Cyclospora cayetanensis - Gerald Sigua; Keith R. Schneider; Renée M. Goodrich; Michael J. Mahovic; Rajya Shukla (EDIS)
Cyclospora cayetanensis is a microscopic, intestinal protozoan parasite first reported in 1979 that has been known as cyanobacterium-like, coccidia-like, and as cyclospora-like bodies (CLB). It wasnt until 1993 that it was officially characterized as Cyclospora cayetanensis. Much is still unknown about C. cayetanensis, but it is a known cause of a gastrointestinal infection (cyclosporiasis), with increasing worldwide incidence including cases in the United States and Canada. This document is FSHN0519, one of a series of the Food Science and Human Nutrition Department, UF/IFAS Extension. Original publication date September 2005.